2020
DOI: 10.1002/smj.3217
|View full text |Cite
|
Sign up to set email alerts
|

Organizational change and the dynamics of innovation: Formal R&D structure and intrafirm inventor networks

Abstract: Prior research has argued and shown that firms with more centralized R&D produce broader innovations, but the organizational mechanisms underlying this relationship are underexplored. This gap limits our understanding of whether and how formal R&D structure can be used as a lever to influence research outcomes. To address this question, we study the relationship between formal R&D structure, internal inventor networks, and innovative behavior and outcomes. We find that centralization of R&D budget authority in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 80 publications
(126 reference statements)
2
40
0
Order By: Relevance
“…In contrast, the literature on the organization of R&D has emphasized the advantages of centralizing the R&D function in a single location. Centralization allows firms to benefit from economies of scale in specialized and indivisible human and physical resources (Poppo, 2003 ), and to reap economies of scope in large R&D laboratories where R&D activities span a diverse set of complementary technology fields (Argyres & Silverman, 2004 ; Argyres et al, 2020 ; Arora et al, 2011 ; Henderson & Cockburn, 1996 ; Leten et al, 2007 ). Furthermore, it has been argued that central R&D units conduct research that is more fundamental and scientific in orientation (Arora et al, 2011 ), and that the collocation of central R&D and corporate IP units offers advantages in terms of stronger control of knowledge (leakages) and more effective appropriation strategies (Collis et al, 2007 ; Di Minin & Bianchi, 2011 ).…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the literature on the organization of R&D has emphasized the advantages of centralizing the R&D function in a single location. Centralization allows firms to benefit from economies of scale in specialized and indivisible human and physical resources (Poppo, 2003 ), and to reap economies of scope in large R&D laboratories where R&D activities span a diverse set of complementary technology fields (Argyres & Silverman, 2004 ; Argyres et al, 2020 ; Arora et al, 2011 ; Henderson & Cockburn, 1996 ; Leten et al, 2007 ). Furthermore, it has been argued that central R&D units conduct research that is more fundamental and scientific in orientation (Arora et al, 2011 ), and that the collocation of central R&D and corporate IP units offers advantages in terms of stronger control of knowledge (leakages) and more effective appropriation strategies (Collis et al, 2007 ; Di Minin & Bianchi, 2011 ).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…This ties in with the notion that R&D activities are typically characterized by strong scale economies, due to the presence of indivisible resources, such as laboratory equipment and specialized human capital (Kuemmerle, 1998 ). Empirical evidence on the organization of R&D has suggested that firms can benefit from conducting R&D in fewer locations, allowing for greater centralization (Argyres & Silverman, 2004 ; Argyres et al, 2020 ; Belderbos et al, 2013 ; Chacar & Lieberman, 2003 ). Centralization of R&D efforts enables firms to spread the high cost of specialized equipment and human capital and to reach the critical mass that is needed to efficiently utilize these resources (Poppo, 2003 ).…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of modern researchers have devoted their scientific works to innovation policy [4][5][6][7]. In this vein, the analysis of the meaning and impact of network theory and the network approach refers to the key issues of modern innovation policy [8][9][10][11][12][13].…”
mentioning
confidence: 99%